(3cJGH GdCYTGH hefGaYgG ddCeQGVs
(3ChdgG (B:s
(3jfaY ef GdLQH LOkG hgj ef LedI GdCOhjI GdefbjI eY KdK hRfg adad s
(3BNQgG (B:s
(3hCUdg CTO bHVkG heG ai WHYg MGQkG jGHSkG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdWHs